PENERAPAN BAURAN PEMASARAN SEBAGAI STRATEGI PEMASARAN DARI DUSTY ART WEDDING DECORATOR - Wiyanto, Wiyanto (LPPM Politeknik Pajajaran ICB Bandung, 2024)
The wedding industry, especially in the field of wedding decoration, is currently continuing to develop. This makes the competition between decoration vendors very tight. In order to survive, companies need to create the right marketing strategy. This study aims to determine the implementation of the right marketing strategy by a company that has survived for a long time in this industry. The research method uses qualitative descriptive analysis through interviews, direct observation, and documentation. Dusty Art Wedding Decoration is an international wedding decoration provider company that has been operating for more than 10 years in the city of Bandung. The marketing strategy is carried out effectively and efficiently by implementing a 4 P marketing mix. The products provided can be adjusted to the client's wishes, the prices offered are cheaper, distribution channels are carried out effectively, and promotions are both conventional and digital. Dusty Art still has the opportunity to increase its revenue by further optimizing digital marketing.